2018
DOI: 10.1155/2018/3123961
|View full text |Cite
|
Sign up to set email alerts
|

Current Trends in Biomaterial Utilization for Cardiopulmonary System Regeneration

Abstract: The cardiopulmonary system is made up of the heart and the lungs, with the core function of one complementing the other. The unimpeded and optimal cycling of blood between these two systems is pivotal to the overall function of the entire human body. Although the function of the cardiopulmonary system appears uncomplicated, the tissues that make up this system are undoubtedly complex. Hence, damage to this system is undesirable as its capacity to self-regenerate is quite limited. The surge in the incidence and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 289 publications
0
4
0
1
Order By: Relevance
“…Moreover, repopulated decellularized liver scaffolds often lack an intact vascular network, and bear the risk of post-transplant hemorrhage and thrombosis. But also general aspects like species 55 or the length of scaffold preservation or storage 56 complicate the application of decellularized scaffolds. Therefore, the generation and application of artificial scaffolds can help to overcome these challenges.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, repopulated decellularized liver scaffolds often lack an intact vascular network, and bear the risk of post-transplant hemorrhage and thrombosis. But also general aspects like species 55 or the length of scaffold preservation or storage 56 complicate the application of decellularized scaffolds. Therefore, the generation and application of artificial scaffolds can help to overcome these challenges.…”
Section: Discussionmentioning
confidence: 99%
“…Beberapa dari penyakit ini dapat mengakibatkan kerusakan yang cukup besar pada jaringan organ-organ dan kadangkadang dapat menyebabkan kerusakan yang tidak dapat diperbaiki pada bagianbagian organ tersebut, sehingga mengganggu fungsi keseluruhannya, akibatnya dapat menurunkan kualitas hidup individu yang terdampak. Tugas kedua sistem ini begitu integral, sehingga keadaan penyakit kronis di satu sistem akan selalu mempengaruhi fungsi efisien yang lain (Fakoya et al, 2018).…”
Section: Latar Belakangunclassified
“…To overcome this problem, several strategies have been proposed and demonstrated the ability to tune its mechanical properties; among these, Deng et al (2010) showed that addition of chitosan is sufficient to increase the compression modulus of collagen fibrils (Geng et al, 2018). Indeed, the compression modulus of the collagen increases when combined with chitosan or elastin, whereas its tensile modulus is reduced, conferring greater stability to the heart and minimizing the ventricular wall dilatation (Fakoya et al, 2018). On this regard, it is worth mentioning the very recent work from Lee et al (2019), who developed the FRESH methodology to 3D-bioprint collagen with improved mechanical properties, allowing the fabrication of cardiac components of different sizes.…”
Section: Engineered Cardiac Tissue Constructsmentioning
confidence: 99%